"Planned greenspace" or "natural greenspace" in a high-density city with compact environment? An empirical study of osteoporosis among senior population. (1st July 2022) - Ho, Hung Chak; Wang, Dan; Leung, Jason; Yu, Blanche; Woo, Jean; Yui Kwok, Timothy Chi; Lau, Kevin
Abstract: Osteoporosis is a major physical health issue in healthy ageing among urban populations. However, few studies have investigated how greenspace can influence osteoporosis, especially to those who lived in a compact city with high-density living environment. Furthermore, no studies have investigated how "planned greenspace" and "natural greenspace" can separately influence osteoporosis among senior population. We hereby conducted an empirical study to evaluate the relationship between osteoporosis, "planned greenspace" and "natural greenspace", based on the use of land use data derived from local geospatial information and satellite images. Our results showed that seniors who were 1) aged, 2) female, 3) less educated, 4) smokers, and 5) with chronic respiratory diseases were associated with osteoporosis. Considering factors of greenspace, a higher percentage of planned greenspace surrounding the residence may be a protective factor while natural greenspace did not influence the individuals. Specifically, a 10% increase of planned greenspace within the 600-m radius area surrounding the residence was negative associated with osteoporosis (−2.8% [-5.1%, −0.5%]). Based on our results, development of planned greenspace may be necessary, as compact built environment of a high-density city often resulted in a lack of planned greenspace for physical activities. Along with the World Health Organization (WHO) guidelines for an age-friendly city, our findings suggest that improving the planned greenspace in a walkable distance around one's neighboring environment is a potential strategy for prevention of osteoporosis and related physical health issues as well as for life quality improvement among the senior population. Highlights: Association of greenspace and osteoporosis in a high-density city. Planned space in compact environment may not have an extensive cover of greenery. Natural greenspace in a high-density city may be inaccessible. More planned space in compact environment may reduce osteoporosis. Natural greenspace may be unable to reduce osteoporosis risk due to inaccessibility.